2010
DOI: 10.1080/15475441.2010.484380
|View full text |Cite
|
Sign up to set email alerts
|

A Single Word in a Population of Words

Abstract: Carey and Bartlett introduced a new method for studying lexical development, one of presenting the child with a word and a single context of use and asking what was learned from that one encounter. They also reported a then new finding: By using what they already knew about previously learned words, young children could narrow the range of possibilities for likely meanings in a single encounter. This papers honors that original contribution and the robust literature and set of phenomena it generated by conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Although this may, in part, be due to environmental factors that promote the usage of color words with young children, such as a focus on color terms by the parents or an increase in colored plastic toys around the home, it is more likely reflective of a difference in measurement sensitivity. Parents are very sensitive to infants understanding and production of specific words (Hidaka & Smith, 2010) and have the opportunity to see them comprehend and produce words in a variety of contexts. In contrast, an early comprehension of color words is much harder to assess, unless explicitly tested, and the contexts in which they are used are far more limited, so the earliest point of comprehension of color terms is much more difficult to ascertain (Ramscar, Thorpe, & Denny, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although this may, in part, be due to environmental factors that promote the usage of color words with young children, such as a focus on color terms by the parents or an increase in colored plastic toys around the home, it is more likely reflective of a difference in measurement sensitivity. Parents are very sensitive to infants understanding and production of specific words (Hidaka & Smith, 2010) and have the opportunity to see them comprehend and produce words in a variety of contexts. In contrast, an early comprehension of color words is much harder to assess, unless explicitly tested, and the contexts in which they are used are far more limited, so the earliest point of comprehension of color terms is much more difficult to ascertain (Ramscar, Thorpe, & Denny, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…cup ) appear to follow an extended developmental trajectory, changing well into young-adulthood (Ameel et al, 2008). This representational change is likely related to variability in the exemplars children are exposed to, variability in the contexts in which they are seen, and to the other words children have learned and the kinds of hypotheses they have entertained (Hidaka & Smith, 2010; Dautriche & Chemla, 2014). Thus, a full understanding of the processes of early word learning will necessarily require further analyses of the natural ecology of word learning and how it changes across development.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson, Frank, Demuth, and Jones (2010) similarly showed that joint inference of words and syllables produces better speech segmentation than does inference over syllables alone. Hidaka and Smith (2010) showed that learning the features relevant for multiple natural language categories allows rapid acquisition of new categories and may help to explain fast-mapping. Because language contains structure at multiple levels and regularities are related across levels, learning something about one level is informative about aspects at other levels.…”
Section: Bootstrapping From Partial Knowledgementioning
confidence: 99%
“…Similarly, although objects that receive a given label are not identical, they typically vary along predictable dimensions (Hidaka & Smith, 2010). Thus, even though L.…”
Section: Bootstrapping From Partial Knowledgementioning
confidence: 99%